Risk Factors of Postoperative Shoulder Imbalance in Adolescent Idiopathic Scoliosis: The Role of Sagittal Spinopelvic Parameters and Upper Instrumented Vertebrae Selection. Issue 1 (February 2022) - Moorthy, Vikaesh; Goh, Graham S.; Guo, Chang-Ming; Tan, Seang-Beng; Chen, John Li-Tat; Soh, Reuben Chee Cheong
Abstract : Study Design: This is a retrospective study. Objective: To determine (1) the independent risk factors of postoperative shoulder imbalance (PSI) after adolescent idiopathic scoliosis (AIS) correction surgery; and (2) whether the level of upper instrumented vertebrae (UIV) affects postoperative shoulder balance. Summary of Background Data: PSI is an important outcome of AIS correction surgery as it influences a patient's appearance and satisfaction. However, risk factors for PSI remain controversial and there are currently no studies evaluating the effect of sagittal spinopelvic parameters on PSI. Previous studies on the relationship between the level of UIV and PSI have also reported conflicting results. Materials and Methods: Sixty-nine AIS patients undergoing correction surgery at a single institution were retrospectively reviewed. Radiographic parameters were measured on anteroposterior and lateral x-rays preoperatively, immediate postoperatively, and 12 months postoperatively. At 1 year follow-up, patients were divided into 2 groups based on their radiographic shoulder height (RSH): (1) PSI group (RSH ≥20 mm) and (2) non-PSI group (RSH <20 mm). Results: On multivariate regression analysis, a lower postoperative main thoracic curve (MTC) [odds ratio (OR): 0.702, 95% confidence interval (CI): 0.519–0.949, P =0.022], greater percentage correction of MTC (OR: 1.526, 95% CI: 1.049–2.220, P =0.027) and higher postoperative sacral slope (OR: 1.364, 95% CI: 1.014–1.834, P =0.040) were identified as independent risk factors of PSI. When preoperative, postoperative, and absolute change in shoulder parameters were compared across the level of UIV, no significant differences were found regardless of the radiographic shoulder parameter analyzed. Conclusions: Lower postoperative MTC, greater percentage correction of MTC and higher postoperative sacral slope were independent risk factors of PSI. Shoulder balance and symmetry were not affected by the level of UIV selected. Relative curve correction is a more important consideration than UIV to avoid PSI after AIS correction surgery. Level of Evidence: III.